2001
DOI: 10.2355/isijinternational.41.965
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Molten Iron with Magnesium Vapor Produced In-situ by Aluminothermic Reduction of Magnesium Oxide.

Abstract: Magnesium vapor produced in-situ by aluminothermic reduction of magnesium oxide was injected directly into the melt with argon carrier gas to desulfurize molten iron to an ultra-low sulfur concentration in a short time.The desulfurization rate increased with increasing temperature in the range from 1 553 to 1 773 K. The desulfurization efficiency of pellet increased with decreasing pellet mass. The effects of initial sulfur concentration and carrier gas flow rate on the desulfurization were also investigated.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 8 publications
1
46
0
Order By: Relevance
“…23) Various reductants could act as the reducing agent for MgO, e.g., Al, C, Si. 24) Comparing the reactions of the reduction of MgO in molten slag and in refractory material, the reaction in molten slag is more dominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23) Various reductants could act as the reducing agent for MgO, e.g., Al, C, Si. 24) Comparing the reactions of the reduction of MgO in molten slag and in refractory material, the reaction in molten slag is more dominant.…”
Section: Discussionmentioning
confidence: 99%
“…desulphurization with magnesium, can be written as: 24) Mg ( The image of a MgS inclusion embedded in a ferrite matrix is shown in Fig. 2.…”
Section: )mentioning
confidence: 99%
“…[1][2][3][4] The present study proves the possibility on the basis of 30 kg scale experiments. Conbination of dilution of magnesium gas by argon gas and use of the injector which has 6 narrow exit holes allows to obtain magnesium efficiency of 74 % at a quantity of magnesium of 0.2 kg per ton hot metal at the initial sulfur content of 0.02 mass%.…”
mentioning
confidence: 51%
“…In steelmaking processes, reduction of slag and dust as well as recycle and treatment of these by-products are important subjects. Magnesium desulfurization of hot metal itself is a well known technology, 5) but Yang et al [1][2][3][4] have shown a possibility of highly efficient magnesium desulfurization of hot metal as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the decrease to the generation of magnesium gas in the vicinity of the tuyeres. Yang et al, [6][7][8][9][10] who are studying the desulfurization of molten iron using the magnesium gas generated from carbon and magnesium oxide in the steelmaking process, report that this desulfurization is highly effective.…”
Section: Introductionmentioning
confidence: 99%